Parenting aspiration among diverse sexual orientations and gender Identities in Mexico, and Its Association with internalized homo/transnegativity and connectedness to the LGBTQ Community - Salinas-Quiroz, Fernando (2019)
The purpose of this study was to examine parenting aspiration among a sample of 1,995 childless cisgender, transgender, monosexual (gay/lesbian), and plurisexual (bisexual/pansexual/queer) Mexican individuals, which were compared according to their gender identity (cisgender vs. transgender) and sexual orientation (monosexual vs. plurisexual). For monosexual individuals, only being in a relationship and gender were significantly associated with parenting aspiration whereas for plurisexual individuals, gender, LGBTQ